Investigação da atividade antiparasitária do Allium sativum L. in vitro e in vivo - Lima, Caliandra Maria Bezerra Luna (2011)
Introduction: Garlic (Allium sativum L) has been used for thousands of years for various therapeutic purposes, including the anti-parasite activity. Aims: The aim of this work is, to analyze the possible anti-parasite effects of Allium sativum through in vitro studies by electron scanning microscopy using Schistosoma mansoni and investigates the Allium sativum L activities in patients with ascariasis, ancylostomiasis, amebiasis and giardiasis, as well to determine the profile of a coproparasitologic community in Cabedelo-PB, location of patient selection. Methodology: To perform in vitro tests, adult male worms of Schistosoma mansoni obtained from infected Swiss Webster mice were treated with Allium sativum L oil at concentrations of 0, 5, 10, 15, 20 mg /ml. Then, they were analyzed by scanning electron microscopy. For tests in vivo, studies were conducted with the selection of infected volunteers, and the PSF III of Renascer in Cabedelo, a suitable place to the project. The first step towards to the achievement consisted of educational speeches and, after signing the free consent form, were distributed fecal-test cups. The fecal examinations were performed at the Laboratory of Clinical Parasitology at the Federal University of Paraíba. In the next step we selected women with ascariasis, ancylostomiasis, giardiasis and amebiasis without anti-parasite treatment. Later, physical examinations and medical tests were performed to determine the biochemical and hematological parameters in order to select individuals able to participate in our research. After selection, the volunteer subjects were treated daily in the morning during 15 days with Allium sativum L oil capsules (Soybean Oil 247.4 mg and 2.6 mg of Allium sativum L essential oil) and were followed and monitored for ingestion. In previously scheduled dates, the feces were collected at the 8th and 16th days after the initial intake for the examinations using the methods of Hoffman, Kato-Katz and Ritchie. Results: In vitro tests, treatment with Allium sativum L oil caused damage to the integument of the worm at all concentrations. A concentration of 5 mg/mL caused wrinkling in the tegument; a concentration of 10 mg/mL resulted in changes to tubercles and loss or modification of spines. With 15 and 20 mg/mL increasing damage to the tegument could be seen, such as vesicle formation and the presence of ulcers. The profile of the coproparasitology community of Renascer III revealed the following results: Of 130 samples analyzed, 104 (80%) were female and 26 (20%) were male. There were 64 (49,2%) negative end 66 (50,8%) positive. The frequency of intestinal parasites were: A. lumbricoides 13,1%; T. trichiura 3,8%; Ancylostomidae 2,3%; S. stercoralis 0,7%; S. mansoni 0,7%; E. nana 30,8%; E. histolytica/E. dispar 13,8%; E. coli 10,0%; G. intestinalis 3,1%; I. bustchlii 1,5%. For treatment with Allium sativum L oil capsules during 15 days, was selected a sample of 23 infected patients, of whom 11 with amebiasis, 9 with ascariasis, 2 with giardiasis and with 1 ancylostomiasis. In vivo tests on the 8th day of treatment, all patients had positive results. On the 16th day, 2 patients had negative results, being parasitized by E. histolytica / E. dispar. Conclusions: Allium sativum acts on the adult worms of Schistosoma mansoni without inducing their death, but being able to promote major skin disorders. Oral administration of Allium sativum L oil capsules, showed no anti-parasite action in the experimental conditions of this study.